Showing off to the new neighbors? Income, socioeconomic status and consumption patterns of internal migrants - Alexander M. Danzer; Barbara Dietz; Kseniia Gatskova; Achim Schmillen (Institut für Ost- und Südosteuropaforschung (IOS), 2013)
This paper analyses incomes and socioeconomic status of internal migrants over time and in comparison to their new neighbors and investigates whether status consumption is a way for newly arrived city dwellers to signal their social standing. Using a novel dataset from the emerging economy of Kazakhstan we find that internal migrants earn an income and status premium for their move. In a comparison to indigenous city dwellers their earnings and household incomes are not significantly different; however, mobile households report a significantly higher subjective socio-economic status. Exploiting expenditure data, we find that recent migrant households gain status from using visible consumption to impress their new neighbors. This signaling might be used as adaptation to the new economic and social environment or to gain access to social capital.
urn:nbn:de:101:1-201307308949
Keywords: P36; I31; R23; 330; Absolute and relative welfare; income; status consumption; conspicuous consumption; signaling model; adaptation; internal migration; rural-urban migration; emerging economy; Kazakhstan; socioeconomic status